Прості сильно зв'язні сагайдаки та їх власні вектори - Дудченко, І.В.; Кириченко, В.В.; Плахотник, М.В. (Український математичний журнал, 2012)
Изучается связь между изоморфизмом колчанов и свойствами их спектров. Доказано, что простые сильно связ- ные колчаны на не более чем четырех вершинах изоморфны тогда и только тогда, когда их характеристические многочлены совпадают, а нормированные левые и правые положительные собственные векторы, соответствующие индексу, равны с точностью до перестановки их координат. Приведен пример, показывающий, что это утверждение не выполняется для колчанов с пятью вершинами. We study the relationship between the isomorphism of quivers and properties of their spectra. It is proved that strongly connected simply laced quivers with at most four vertices are isomorphic to one another if and only if their characteristic polynomials coincide and their left and right normalized positive eigenvectors that correspond to the index can be obtained from one another by the permutation of their coordinates. An example showing that this statement is not true for quivers with five vertices is given.